2011
DOI: 10.1186/1743-7075-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Cereal based diets modulate some markers of oxidative stress and inflammation in lean and obese Zucker rats

Abstract: BackgroundThe potential of cereals with high antioxidant capacity for reducing oxidative stress and inflammation in obesity is unknown. This study investigated the impact of wheat bran, barley or a control diet (α-cellulose) on the development of oxidative stress and inflammation in lean and obese Zucker rats.MethodsSeven wk old, lean and obese male Zucker rats (n = 8/group) were fed diets that contained wheat bran, barley or α-cellulose (control). After 3 months on these diets, systolic blood pressure was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…The existence of a relationship between complications associated to MS and cardiovascular diseases is widely known, being hypertension one of the most important risk factor for development of cardiovascular pathologies (Maraj, Makaryus, Ashkar, McFarlane, & Makaryus, ). In the present study, SBP was slightly higher in 20 weeks‐old ZFR than ZLR, in agreement to that found by other researchers; in fact, ZFR are considered as pre‐hypertensive animals at young ages and hypertensive animals since 25–30 weeks of life (Belobrajdic, Lam, Mano, Wittert, & Bird, ; Oltman et al, ). Neither the HEW1 nor the HEW2 treatment modified blood pressure in ZFR rats in spite of the important in vitro ACE inhibitory and antioxidant activities described for both hydrolysates (Garcés‐Rimón, Lopez‐Expósito, et al, ) and the in vivo effects exerted by HEW1 improving glucose metabolism, obesity‐related oxidative stress, inflammation and steatosis previously observed in ZFR (Garcés‐Rimón, González, et al, ; Garcés‐Rimón et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The existence of a relationship between complications associated to MS and cardiovascular diseases is widely known, being hypertension one of the most important risk factor for development of cardiovascular pathologies (Maraj, Makaryus, Ashkar, McFarlane, & Makaryus, ). In the present study, SBP was slightly higher in 20 weeks‐old ZFR than ZLR, in agreement to that found by other researchers; in fact, ZFR are considered as pre‐hypertensive animals at young ages and hypertensive animals since 25–30 weeks of life (Belobrajdic, Lam, Mano, Wittert, & Bird, ; Oltman et al, ). Neither the HEW1 nor the HEW2 treatment modified blood pressure in ZFR rats in spite of the important in vitro ACE inhibitory and antioxidant activities described for both hydrolysates (Garcés‐Rimón, Lopez‐Expósito, et al, ) and the in vivo effects exerted by HEW1 improving glucose metabolism, obesity‐related oxidative stress, inflammation and steatosis previously observed in ZFR (Garcés‐Rimón, González, et al, ; Garcés‐Rimón et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have shown that cereal grain consumption can lower markers of chronic disease. A study done with lean and obese Zucker rats showed that wheat bran consumption lowered plasminogen activator inhibitor‐1 levels in the obese rats to the levels observed in the lean rats (Belobrajdic and others ). This was partially attributed to antioxidant capacity and the ability for wheat bran to modestly reduce oxidative stress.…”
Section: Cereal Health Benefitsmentioning
confidence: 92%
“…Furthermore, recent pig feeding trials indicate that consumption of arabino-(1→4)-b-D-xylan attenuates the somewhat damaging effect of the western diet on gut health (Belobrajdic et al, 2011). Conversely, (1→3, 1→4)-b-D-glucan also reduces digestibility and hence available metabolizable energy in monogastric animals such as pigs and poultry and lowers extraction potential and reduces filterability during malting and brewing (Brennan and Cleary, 2005).…”
Section: Polysaccharides [In Particular (1→3 1→4)-b-d-glucan and Aramentioning
confidence: 99%